2009
DOI: 10.1016/j.asr.2009.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The Pioneer anomaly and a rotating Gödel universe

Abstract: Based upon a simple cosmological model with no expansion, we find that the rotational terms appearing in the Gödel universe are too small to explain the Pioneer anomaly. Following a brief summary of the anomaly, cosmological effects on the dynamics of local systems are addressedincluding a derivation of the equations of motion for an accelerated Pioneer-type observer in a rotating universe. The rotation or vorticity present in such a cosmological model is then subjected to astrophysical limits set by observati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 65 publications
(74 reference statements)
0
19
0
Order By: Relevance
“…The effect of cosmological expansion on local systems had been studied by a number of authors [21, 82, 118, 137, 202], (for reviews, see [73, 124, 177, 422]). To study the behavior of small isolated mass in expanding universe, one starts with the weak field ansatz [73, 177]: and derives the linearized Einstein equations for h μν : The relevant solution with modified Newtonian potential is given below The first part in Equation (6.20) is the standard Newtonian potential with the measured distance R ( t ) r in the denominator.…”
Section: Efforts To Explain and Study The Anomalymentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of cosmological expansion on local systems had been studied by a number of authors [21, 82, 118, 137, 202], (for reviews, see [73, 124, 177, 422]). To study the behavior of small isolated mass in expanding universe, one starts with the weak field ansatz [73, 177]: and derives the linearized Einstein equations for h μν : The relevant solution with modified Newtonian potential is given below The first part in Equation (6.20) is the standard Newtonian potential with the measured distance R ( t ) r in the denominator.…”
Section: Efforts To Explain and Study The Anomalymentioning
confidence: 99%
“…Wilson and Blome [422] derived the equations of motion for an accelerated, rotating observer in a Gödel universe, and calculated the contribution of the universal cosmic rotation or vorticity. However, they found that this term cannot account for the observed Pioneer acceleration.…”
Section: Efforts To Explain and Study The Anomalymentioning
confidence: 99%
“…Attempts to find exotic gravitational explanations for PA did not even cease after the publication of the latest works on the non‐gravitational effects like Bertolami et al (2008); just to limiting to published works, see e.g. Avramidi & Fucci (2009), Wilson & Blome (2009), Greaves (2009) and Exirifard (2009). A dedicated spacecraft‐based mission to test the PA in the outer regions of the Solar system has also been proposed and investigated (Dittus et al 2005; Rathke & Izzo 2006; Bertolami & Páramos 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Within the errors, the directions of Ψ are orthogonal to each other. Local, astronomical consequences of the Gödel (1949) model have been recently investigated in Wilson & Blome (2009) by looking for a possible explanation of the Pioneer anomaly occurring in the remote regions of the solar system. mass shell, and of their Machian impact have been produced (Bičák et al 2004;Schmid 2001Schmid , 2006Schmid , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…In all the cases considered so far, a rotation is induced with respect to a locally quasi-inertial Fermi frame; thus, a Coriolis-type acceleration 8 affecting the motions of test particles moving with respect to it arises (Wilson & Blome 2009). See, e.g., Silk (1966) for early studies of the Coriolis and centrifugal accelerations acting on a test particle moving in the Gödel spacetime.…”
Section: Introductionmentioning
confidence: 99%